Mechanical efficiency during a cycling test is not lower in children with excess body weight and low aerobic fitness1. (16th March 2013) - Jabbour, Georges; Lambert, Marie; O'Loughlin, Jennifer; Tremblay, Angelo; Mathieu, Marie‐Eve
Abstract Objective: The aims of this study were to assess the association between (i) body weight status and mechanical efficiency (ME); and (ii) ME and aerobic fitness in children aged 8‐10 years. Design and Methods: The sample included 464 prepubertal children (258 boys). A total of 288 were normal‐weight (NW); 84 overweight (OW); and 92 obese (OB). Subjects performed an incremental maximal cycling test with indirect calorimetry. MEcrude (%) was calculated for the first five stages of the protocol (25, 50, 75, 100, and 125 W) as follows: work produced, in watts total energy consumption, in watts−1·100−1. For MEnet, resting energy consumption was subtracted from total energy consumption. Energy consumption was calculated as follows: (4.94·respiratory exchange ratio + 16.04) · VO2, in ml·min−1·60−1. Results: MEcrude was significantly higher in NW compared to OW and OB children and in OW compared to OB children at 25, 50, 75, 100, and 125 W. In contrast, MEnet did not differ significantly among NW, OW, and OB children. No statistically significant association was found between crude or net ME and peak oxygen consumption (VO2peak; in ml·kg−1·min−1); therefore, the ability to transfer chemical energy to mechanical work is maintained in children aged 8‐10 years old regardless of body weight status and aerobic fitness. Moreover, higher values of MEcrude during exercise are explained by elevated oxygen consumption at rest and not by energy consumed during physical activity. Conclusions: These results highlight that prepubertal children are equally efficient since they are able to perform a physical task such as cycling using the same proportion of energy regardless of their body weight status.